A duração razoável do processo na justiça do trabalho: uma abordagem constitucional - Teixeira, Winston de Araújo (2017)
The present dissertation deals with the reasonable length of the process, specifically, in labor justice. In this context, we address the constitutional issues regarding the problematization of the reasonable duration of the process, as a fundamental right, as well as its applicability in labor justice. The study of the chosen topic is important because it brings the discussion about the "delay" in the jurisdictional provision, notably to the one that assures the fundamental rights of the workers, providing the analysis of the causes and consequences of the time of the process. The present work aims to develop a constitutional approach to the reasonable length of the process in labor justice, considering the reasonable time of the process in the Brazilian legal system as a fundamental right. The problem of the effects of time on the jurisdictional activity and the growing phenomenon of the summarization of procedural cognition, where the process of extensive knowledge begins to be seen as a residual way to solve conflicts. Using the technique of indirect documentation, through a bibliographical research, the design of reasonable time of the process appropriate to the process of the country is analyzed; the relationship between efficacy, effectiveness, legal certainty and the reasonable time of judicial service; the formal validation of the reasonable duration of the process in the Federal Constitution of 1988, in international law and in some Latin American countries; and the immediate applicability of this fundamental right. The theme is developed based on the constitutional bias of fundamental rights interpretation and constitutional principles, an approach that will always have the concern of being guided by a methodology that contemplates normative, empirical-dogmatic and fundamental right to time process. The study of this problematic in the judicial scope, more specifically, in the field of the labor process, is adopted as methodological section. The crisis of the Judiciary and procedural delays are indicated as problems directly related to the limits and possibilities of realization of the fundamental right under study. Finally, in an analytical and critical view, the conclusions are presented, which demonstrate the alternatives and / or mechanisms that can be used in overcoming the limits imposed to the immediate realization of the fundamental right to the reasonable time of the process in the labor courts.